2023
DOI: 10.1002/pssb.202200611
|View full text |Cite
|
Sign up to set email alerts
|

First‐Principles Modeling of the Adsorption Mechanism of Carboxylic and Phosphonic Acids onto Pristine and Defective Delafossite CuAlO2 Surfaces

Abstract: In order to provide atomistic insights on the mechanism and stability of dye grafting to delafossite surfaces, the authors study, using density‐functional theory calculations in vacuo and in implicit solvent, the adsorption of carboxylic and phosphonic anchoring groups onto stoichiometric and defective slabs exposing the most stable (012) termination. A remarkable increase of the adsorption energies is found on the reduced surfaces when the vacancy is on the top surface layer, in proximity to the molecule. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 104 publications
0
0
0
Order By: Relevance
“…The most significant result from these desorption experiments, with respect to selecting a system for photochemical studies, is that 3-SeP persisted on the surface of CuAlO 2 during prolonged immersion in acetonitrile. This result is consistent with recent computational studies by Fatihi et al, who reported that calculated adsorption energies for methylphosphonic acid were 18-to-33% greater than for benzoic acid, on both the pristine (012) surface of CuAlO 2 and a (012) surface with Cu(I) vacancies. The greater adsorption energy of the phosphonic acid, relative to the carboxylic acid, would give rise to an increased activation energy for desorption, which is consistent with our experimental data revealing that 3-SeP is more inert than 1-Se-1 on CuAlO 2 .…”
Section: Resultssupporting
confidence: 92%
“…The most significant result from these desorption experiments, with respect to selecting a system for photochemical studies, is that 3-SeP persisted on the surface of CuAlO 2 during prolonged immersion in acetonitrile. This result is consistent with recent computational studies by Fatihi et al, who reported that calculated adsorption energies for methylphosphonic acid were 18-to-33% greater than for benzoic acid, on both the pristine (012) surface of CuAlO 2 and a (012) surface with Cu(I) vacancies. The greater adsorption energy of the phosphonic acid, relative to the carboxylic acid, would give rise to an increased activation energy for desorption, which is consistent with our experimental data revealing that 3-SeP is more inert than 1-Se-1 on CuAlO 2 .…”
Section: Resultssupporting
confidence: 92%